2021
DOI: 10.21203/rs.3.rs-301490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexmedetomidine reduces the incidence of postoperative delirium after cardiac surgery: A meta-analysis of randomized controlled trials

Abstract: Background The role of dexmedetomidine in preventing delirium after cardiac surgery remains controversial because of several recent trials with negative results. We aimed to perform an updated meta-analysis of randomized controlled trials (RCTs) to clarify this controversy. Methods RCTs investigating the perioperative administration of dexmedetomidine in cardiac surgery were retrieved from PubMed, Web of Science, and the Cochrane library until August,27,2020. Two researchers independently screened the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Postoperative delirium (POD) remains an important topic in clinical research, as up to 53% of patients who undergo major surgery have been shown to experience some level of cognitive dysfunction. 1 Multiple publications over the last year attempted to identify predictors of postoperative delirium, examining risk factors throughout the perioperative period.…”
Section: Postoperative Deliriummentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative delirium (POD) remains an important topic in clinical research, as up to 53% of patients who undergo major surgery have been shown to experience some level of cognitive dysfunction. 1 Multiple publications over the last year attempted to identify predictors of postoperative delirium, examining risk factors throughout the perioperative period.…”
Section: Postoperative Deliriummentioning
confidence: 99%
“…Falk et al 3 Preoperative diagnosis of depression is a prevalent and potentially modifiable risk factor for POD. Li et al 1 Dexmedetomidine provides adequate sedation and reduces POD compared to other common sedatives.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several meta-analyses have been published on this topic in recent years (Table 3). An updated meta-analysis by Li et al , which searched through August 2020 and incorporated DECADE and DEXACET, found strong summary evidence for dexmedetomidine's role in reducing delirium after cardiac surgery [23 ▪▪ ]. This meta-analysis attempted to separate effective and ineffective trials by performing several subgroup analyses, recognizing that the substantial heterogeneity in population and dose created unfortunate complexity to the message for clinicians.…”
Section: Meta-analysis: Trials and Tribulationsmentioning
confidence: 99%
“…Dexmedetomidine (DEX) is a selective α-2 agonist that downregulates the release of norepinephrine in the central nervous system without suppressing breathing [19]. It is being widely used with good safety in CS patients [20,21]. And it is the standard sedation protocol adopted at Zhongshan Hospital, Fudan University.…”
Section: Introductionmentioning
confidence: 99%